Rotating-mirror Q-switched Er:YAG laser for optodynamic studies - Bizjak, Aleš (Strojniški vestnik, 2011)
In this article a development of a simple, reliable and repeatable Q-switched Er:YAG laser with a pulse duration of 270 ns and energies up to 16 mJ in a TEM00 spatial beam mode is presented. The Q-switching is performed mechanically with a flat, highly reflective silicon rotating mirror. The laser pumping chamber is cooled with thermally stabilized de-ionized water. This laser is intended for optodynamic studies of the short Er:YAG laser pulses with various media, primarily those containing water, where the thermal diffusion effects are negligible.
Keywords: Er:YAG laser; inverse population; laserji; optodinamika; optodynamics; Q-switch; rotating mirror; termično lečenje; vrteče zrcalo; Xe flash lamp